Pregnancy and brain architecture: Associations with hormones, cognition and affect. (10th January 2022) - Rehbein, Elisa; Kogler, Lydia; Kotikalapudi, Raviteja; Sattler, Anna; Krylova, Marina; Kagan, Karl Oliver; Sundström‐Poromaa, Inger; Derntl, Birgit
Abstract: Sex hormones such as estradiol (E2) have long‐lasting influence on brain architecture. Recent studies indicate further structural changes during hormonal transition periods including pregnancy, when women experience the greatest increase in sex hormone levels across their life span. In the present study, three groups of women ( n  = 44) with different levels of E2 underwent structural magnetic resonance imaging: (1) first‐time pregnant women ( n  = 13, 'extreme E2 group'); (2), nulliparous, naturally cycling women who received 12 mg of E2 valerate ( n  = 16, 'high E2 group'); and (3) nulliparous, naturally cycling women receiving a placebo and hence low E2 ( n  = 15, 'low E2 group'). Blood samples were taken to assess hormonal levels. Moreover, parameters for cognition, emotion regulation and affect were assessed. On the neuronal level, the extreme E2 compared to the high E2 group showed a reduced gray matter volume in the left putamen. However, no significant differences were found between the low vs. high E2 groups, nor between the low E2 and extreme E2 groups. Cognitive performance was reduced in the extreme E2 group, although a positive affect was increased compared to the high E2 and low E2 groups. Furthermore, regression analyses revealed several associations between cognition, subjective measures of affect, emotion regulation and gray matter volume. A volume reduction of the left putamen during pregnancy further supports the notion that the female brain is shaped by hormonal transition phases, possibly preparing women for their future roles (e.g., pregnant women for their role as mothers). Abstract : In the present study, three groups of women ( n  = 44) with different levels of estradiol (E2) underwent structural magnetic resonance imaging: (1) first‐time pregnant women ( n  = 13, 'extreme E2 group'); (2), nulliparous, naturally cycling women who received 12 mg of E2 valerate ( n  = 16, 'high E2 group'); and (3) nulliparous, naturally cycling women receiving a placebo and hence low E2 ( n  = 15, 'low E2 group'). On the neuronal level, the extreme E2 compared to the high E2 group showed a reduced gray matter volume in the left putamen. A volume reduction of the left putamen during pregnancy further supports the notion that the female brain is shaped by hormonal transition phases, possibly preparing women for their future roles (i.e., pregnant women for their role as mothers).